The impact of social media use and online word-of-mouth on consumers' purchase decisions, using trust as a mediator - Muhamad Luthfi; Yunita Engriani (Universitas Negeri Padang, 2023)
This study aims to analyze the effect of social media usage and electronic word of mouth on purchase decisions with trust as a mediating variable for Orion coffee shop Padang consumers. The research population is consumers who shop for the first time at Orion Coffee Shop Padang. The number of samples in this study were 150 respondents. Data was collected by distributing questionnaires online via google form and data processing was carried out using the SmartPLS software. The results of this study indicate that (1) social media usage has a positive and significant effect on purchase decision, (2) electronic word of mouth has a positive and significant effect on purchase decision, (3) social media usage has a positive and significant effect on trust, (4) electronic word of mouth has a positive and significant effect on trust, (5) trust has a positive and significant effect on purchase decision, (6) social media usage has a positive and significant effect on purchase decision through trust as mediating variable, (7) electronic word of mouth has a positive and significant effect on purchase decision through trust as a mediating variable